PRESIDENCY OF THE REPUBLIC OF CROATIA TO THE COUNCIL OF THE EUROPEAN UNION IN 2020 : A CHALLENGE FOR THE REPUBLIC OF CROATIA (EU and comparative law issues and challenges series (ECLIC), 2019)
The Republic of Croatia will chair the Council of the European Union from 1 January to 30 June 2020, within the framework of the Joint Presidency Programme with Romania and Finland for a period of 18 months. On 5 July 2018, the Government of the Republic of Croatia adopted a Decision on the Establishment of the Structure for the Preparation and Implementation of the Presidency of the Republic of Croatia of the Council of the European Union in 2020 and declared all preparatory activities for the Presidency to be of special importance for the Republic of Croatia. It is anticipated that around 1,400 meetings will be held in Brussels during the presidency of the Republic of Croatia, along with 1 to 2 summits of Heads of State and Government of the EU member states, about 20 meetings and conferences at the ministerial level and about 200 lower level meetings. Given the requirements and the necessary preparatory and especially implementation activities and a relatively short time for preparation and organization, we believe that the presidency will be a major financial, organizational, logistical, personnel and political challenge for the Government and the Republic of Croatia. On the other hand, the presidency is a chance and an opportunity for the Republic of Croatia to influence the creation and direction of common European policies. Since the Slovenia encountered similar challenges when they have been chairing the Council of the European Union for the first time, we will look at their problems and solutions. The purpose of the research is to identify the key challenges and problems the Republic of Croatia will face when organizing and implementing the Presidency of the Council of the European Union. The aim of the paper is to make recommendations and to define the specific conditions that must be met to successfully organize and implement the Presidency of the Republic of Croatia of the Council of the European Union. Establishment of the presented governance structure of the Croatian Presidency can be positively assessed and it can be assumed that for the successful preparation and implementation of the Presidency of the Council, it is good that the members of the governing body are high-ranking government officials who will be able to use their influence to ensure the anticipated priority of the presidency-related affairs in state administration bodies. On the other hand, it is operationally essential to ensure good and continuous cooperation between and within ministries and other state administration bodies. The research methodology will be based on the secondary, desk study, decisions and programme of the Government of the Republic of Croatia and the comparison of programme and results of the Slovenian Presidency.